Quercetin ameliorates paclitaxel-induced neuropathic pain by stabilizing mast cells, and subsequently blocking PKCε-dependent activation of TRPV1 - GAO Wei; ZAN Yan; WANG Zai-jie Jim; HU Xiao-yu; HUANG Fang (Acta Pharmacologica Sinica, 2017)
Aim: Severe painful sensory neuropathy often occurs during paclitaxel chemotherapy. Since paclitaxel can activate mast cell and basophils, whereas quercetin, a polyphenolic flavonoid contained in various plants, which can specifically inhibit histamine release as a mast cell stabilizer. In this study we explore whether quercetin could ameliorate paclitaxel-induced neuropathic pain and elucidated the underlying mechanisms. Methods: Quercetin inhibition on histamine release was validated in vitro by detecting histamine release from rat basophilic leukemia (RBL-2H3) cells stimulated with paclitaxel (10 μmol/L). In the in vivo experiments, rats and mice received quercetin (20, 40 mg·kg-1·d-1) for 40 and 12 d, respectively. Meanwhile, the animals were injected with paclitaxel (2 mg/kg, ip) four times on d 1, 3, 5 and 7. Heat hyperalgesia and mechanical allodynia were evaluated at the different time points. The animals were euthanized and spinal cords and dorsal root ganglions were harvested for analyzing PKCε and TRPV1 expression levels. The plasma histamine levels were assessed in rats on d 31. Results: Pretreatment with quercetin (3, 10, 30 μmol/L) dose-dependently inhibited excessive histamine release from paclitaxel-stimulated RBL-2H3 cells in vitro, and quercetin administration significantly suppressed the high plasma histamine levels in paclitaxel-treated rats. Quercetin administration dose-dependently raised the thresholds for heat hyperalgesia and mechanical allodynia in paclitaxel-treated rats and mice. Furthermore, quercetin administration dose-dependently suppressed the increased expression levels of PKCε and TRPV1 in the spinal cords and DRGs of paclitaxel-treated rats and mice. Moreover, quercetin administration may inhibited the translocation of PKCε from the cytoplasm to the membrane in the spinal cord and DRG of paclitaxel-treated rats. Conclusion: Our results reveal the underlying mechanisms of paclitaxel-induced peripheral neuropathy and demonstrate the therapeutic potential of quercetin for treating this side effect.